2003
DOI: 10.1111/j.1651-2227.2003.tb00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of longitudinal motor development in very low birthweight infants from 5 months to 5.5 years

Abstract: Erikson C, Allert C, Brogren Carlberg E, Katz-Salamon M. Stability of longitudinal motor development in very low birthweight infants from 5 months to 5.5 years. Acta Paediatr 2003; 92: 197-203. Stockholm. ISSN 0803-5253 Aim: The motor performance of 165 very low birthweight (VLBW) infants was assessed prospectively at 5, 10, 18 mo and 5.5 y. The aim of the study was to evaluate longitudinal stability of motor development and its association with birthweight (BW), gestational age at birth, intraventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
1
26
1
6
Order By: Relevance
“…It was observed that there was no child in the full-term group at six months with suspect or atypical development. development (0-10) at the first evaluation were those who were born weighing between 1530 and 1730 grams, with the lowest weight classified with the suspect development (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) in the second evaluation. The premature infant born weighing 1290 grams had a regression in the total score, as at four months its development was considered normal, however, at six months was reclassified as atypical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that there was no child in the full-term group at six months with suspect or atypical development. development (0-10) at the first evaluation were those who were born weighing between 1530 and 1730 grams, with the lowest weight classified with the suspect development (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) in the second evaluation. The premature infant born weighing 1290 grams had a regression in the total score, as at four months its development was considered normal, however, at six months was reclassified as atypical.…”
Section: Resultsmentioning
confidence: 99%
“…Studies claim that newborn premature babies with low birth weight are at high risk for developmental problems and present greater vulnerability for not developing the relevant motor skills in the first months of life (13) . It was observed that the two premature infants who presented atypical Acta Paul Enferm 2011;24(5):670-5. motor development of premature infants (16)(17)(18) . A study conducted with 561 children between 0 and 18 months in the city of Porto Alegre shows that there is a greater range of behavioral variation in the 3 rd (Standard deviation -SD=9.07) and 4 th (SD=7.60) trimesters, with the lower variations occurring in the 6 th (SD = 1.57) and 1 st (SD = 3.30) trimesters (9).…”
Section: Discussionmentioning
confidence: 99%
“…For the experimental group, cognitive tasks were given concurrently while performing the previous gait training exercises. They were selected according to related dual and triple-task research [25][26][27][28][29][30][31] and they were given as follows:…”
Section: Instrumentationmentioning
confidence: 99%
“…McMaster et al [27] Sann and Streri [28] Shin et al [29] Colson et al [1] Gao et al [30] Tan and Tan [20] Young et al [31] Dionisio et al [32] Chaudhari and Deo [9] Hieu et al [33] Philippi et al [34] Pedroso and Rotta [35] Jain et al [36] Ericsson et al [37] Total 10 articles 4 articles Table 1: Summary of study data.…”
Section: Group a Group Bmentioning
confidence: 99%
“…Ericsson et al [37] followed longitudinally the motor development of children from five months to five and a half years. None of fivemonth children evaluated by MAI presented palmar grasp reflex.…”
Section: Dubowitz Newborn Examination: Dubowitz Newborn Examinationmentioning
confidence: 99%